Age Bias in Selection Decisions: The Role of Facial Appearance and Fitness Impressions - Kaufmann, Michèle C.; Krings, Franciska; Zebrowitz, Leslie A.; Sczesny, Sabine (Frontiers in Psychology, 2017)
This research examined the impact of facial age appearance on hiring and impressions of fitness as the underlying mechanism. In two experimental hiring simulations, one with lay persons and one with Human Resource professionals, participants evaluated a chronologically older or younger candidate (as indicated by date of birth) with either younger or older facial age appearance (as indicated by a photograph). In both studies, older-looking candidates received lower hireability ratings, due to less favorable fitness impressions. In addition, Study 1 showed that the age bias was reduced when the candidates provided counter-stereotypic information about their fitness. Study 2 showed that facial age-based discrimination is less prevelant in jobs with less costumer contact (e.g., back office).